Pengukuran Ergonomi Metode Recommended Weight Limit (RWL) Lifting Index (LI) di PT X - Diah Andianingsari; Abdul Rahman; Bayu Nur Kuncoro (LPPM Universitas Bina Sarana Informatika, 2022)
In the activity of lifting the box containing PCC onto the trolly at the MH DC section – Mr. Jailani. manual handling, the frequency of box mobilization is ± 5 times per hour, from the area where the box is filled to the chute. The weight of the load (PCC filled box) that is lifted is in the range of 12 kg - 16.5 kg, with a vertical lift from the conveyor to the top of the third box arrangement which is about ±50 cm. At the exit of the conveyor, the arrangement of boxes containing PCC is made two levels before being transferred to the trolley. The results of ergonomic measurements using the RWL and LI methods are as follows: The LI value for the Box lift point position level 1 with the origin of 1.42 means it has a moderate risk level (LI 1-<3) and an LI value of 1 means it has a moderate risk level (LI 1-<3) The LI value for the Box lift point position level 2 with the origin of 1.02 means it has a moderate risk level (LI 1-<3) and an LI value of 0.94 means it has a low risk level (LI <1) There is a decrease in the value of LI by improving the way of lifting weights so that the level of risk experienced by workers is also lower.